Observations on the liturgical psalter in MS Canon. liturg. 172 (Bodleian Library, Oxford) - MacRobert, Catherine Mary (Array, 2019)
This paper examines presentational and textual peculiarities of the liturgical psalter in the breviary contained in the Glagolitic MS Canon. liturg. 172 in the Bodleian Library. It argues that they demonstrate a heavy reliance on memorization of text, seem to reflect distinctive liturgical practice, and imply that the manuscript was written for a specific user.